Efficient absorption cooling for low district heating return temperatures. (October 2021) - Petersen, S.; Hausherr, Carsten; Hüls, Walther; Paitazoglou, Reuven; Albers, Jan
Abstract: In the past years scientists of Technische Universität Berlin, developed a new generation of single stage H 2 O/LiBr absorption chillers in the range of 50 to 500 kW nominal cooling capacity. In 16 installations 25 absorption chillers have been monitored within a broad field test (F eldtest A bsorptions k älte für Kraft-Wärme-Kälte-Kopplung- S ysteme, FAkS, funded by BMWi as project FKZ 03ET1171a-d) in the years 2013 to 2018. Annual performance figures of thermal coefficient of performance ( C O P t h ) in the range of 0.7 kWh 0 /kWh 2 and electrical coefficient of performance ( C O P e l ) superior to 20 kWh 0 /kWh el have been proven, serving district heat (DH) return line temperatures in the range of 62 °C to 68 °C. While the FAkS project focused on installation and operation of absorption chillers themselves, the follow-up project called ReKs (R egelung e nergie-aufwandsoptimierter K älteerzeugungs s ysteme, FKZ 03ET1583), concentrates on overall system control and efficiency. Controlling absorption chiller cooling supply at low district heat return line temperatures is extended to an energy efficient control of all participating components including hot water, chilled water, heat sink pump and cooling tower fans. Models and strategies have been developed on thermal science theory and implemented in industrial control software. Proof of concept has been evaluated by monitoring field test installations while in parallel particular field test related parameters have been varied. Without diminishing quality of chilled water temperature and/or cooling capacity, electrical energy efficiency can at least be doubled, compared to the figures of FAkS installations. Moreover, new strategies enable efficient absorption cooling with DH return line temperatures in the range of 50 °C during moderate weather conditions periods. Field test results from 2020 and 2021 are presented here.